Pengaruh Kompensasi Terhadap Kinerja Karyawan Pada PT Mora Telematika Indonesia Jakarta (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2020)
This research was conducted because the performance of employees at PT Mora Telematics Indonesia is not optimal so it is suspected that there is an effect of compensation on employee performance at PT Mora Telematics Indonesia Jakarta. This research uses a quantitative approach with correlational research. The study population was 150 employees with a sample of 60 respondents who were taken using simple random sampling technique and data collection techniques using a questionnaire. Simple Linear Regression and Hypothesis Testing were used in this study. Based on the results of the analysis, it is known that there is a positive and significant influence between compensation and performance. Thus H1 is accepted and H0 is rejected. The effect of compensation on performance is indicated by the regression equation Y =. The results also show a correlation coefficient or r of 0.452, which means that there is a moderate relationship between the independent variable, namely compensation to the dependent variable, namely employee performance. Meanwhile, the coefficient of determination or r-square of 0.204 shows that compensation for performance has an effect of 20.4% and the remaining 79.6% is influenced by other variables not observed in this study